Is there an optimal school starting age? - Elizabeth Dhuey; Kourtney Koebel (IZA World of Labor, 2022)
There is a widely held belief that older students, by virtue of being more mature and readier to learn at school entry, may have better academic, employment, and earnings outcomes compared to their younger counterparts. There are understated, albeit important, costs to starting school later, however. Compulsory school-attendance laws may allow these same older pupils to drop out of high school earlier, which could adversely impact their employment; entering the workforce later also has implications for lifetime earnings and remittances to governments. Overall, research suggests that school-age entry policies can improve student achievement in the short term, but the long-term impacts are currently not well-understood.
Keywords: I21; 330; education; age; relative age; test score gap; redshirting